A randomized comparison of chloroquine versus dihydroartemisinin-piperaquine for the treatment of Plasmodium vivax infection in Vietnam - Thuan, PD; Ca, NTN; Toi, PV; Nhien, NTT; Thanh, NV; Anh, ND; Phu, NH; Thai, CQ; Thai, LH; Hoa, NT; Dong, LT; Loi, MA; et al. (American Society of Tropical Medicine and Hygiene, 2016)
A total of 128 Vietnamese patients with symptomatic Plasmodium vivax mono-infections were enrolled in a prospective, open-label, randomized trial to receive either chloroquine or dihydroartemisinin-piperaquine (DHA-PPQ). The proportions of patients with adequate clinical and parasitological responses were 47% in the chloroquine arm (31 of 65 patients) and 66% in the DHA-PPQ arm (42 of 63 patients) in the Kaplan-Meier intention-to-treat analysis (absolute difference 19%, 95% confidence interval = 0-37%), thus establishing non-inferiority of DHA-PPQ. Fever clearance time (median 24 versus 12 hours, P = 0.02), parasite clearance time (median 36 versus 18 hours, P < 0.001), and parasite clearance half-life (mean 3.98 versus 1.80 hours, P < 0.001) were all significantly shorter in the DHA-PPQ arm. All cases of recurrent parasitemia in the chloroquine arm occurred from day 33 onward, with corresponding whole blood chloroquine concentration lower than 100 ng/mL in all patients. Chloroquine thus remains efficacious for the treatment of P. vivax malaria in southern Vietnam, but DHA-PPQ provides more rapid symptomatic and parasitological recovery.